Understanding place attachment in temporary public space through noematic-noetic synthesis (ARTEKS : Jurnal Teknik Arsitektur, 2022)
To create a successful temporary public space that can sustain in dealing with the contemporary changes, particularly during this pandemic era which is full of uncertainty, the degree of people’s attachment to that place should be maintained. It is simply because the more the public space is needed, the more users will use the space, and a sense of belonging will grow to help maintain its sustainability afterward. The temporality aspect of time, nevertheless, can affect the growth of a person’s place attachment. Using Husserl’s phenomenological analysis of noema and noesis, this qualitative study intends to understand the place attachment development in one of the notorious temporary public spaces in Indonesia, a Ramadan street market, particularly in Batam. Direct observation and semi-structured interviews were conducted to collect the data regarding the theoretical framework of place attachment obtained from the literature review. This study reveals that, through the noematic synthesis, the external dimensions (physical characteristic) most likely lead to functional attachment or place dependence. Whilst through the noetic synthesis, the psychological attachment or place identity of the temporary public space can be influenced by the internal dimensions of place attachment (social intercourse, social cohesion, and social symbol).
Keywords: Noema noesis; Place attachment; Public space; Ramadan street market; Temporary